The Complete Letters of Henry James, 1884-1886 Volume 2. - James, Henry (The Complete Letters of Henry James., 2021)
This fifteenth installment in the complete collection of Henry James's more than ten thousand letters records James's ongoing efforts to care for his sister, develop his work, strengthen his professional status, build friendships, and engage timely political and economic issues.